An Analysis of the Pre and Post Harvest Management Techniques in Rice Production: The Case of Unvda Ndop, North West Region, Cameroon - M. J, Bime; N. M, Ngala; A. F, Jaza; M.L, Mawo (International Journal of Sustainable Agricultural Research, 2015)
This paper examines the adoption of improved pre and post harvest management techniques with a view to finding means to improve on the livelihood of rice farmers. These farmers were selected from two divisions (Bui and Ngoketunjia) where rice is being produced by the Upper Nun Valley Development Authority (UNVDA) in the North West Region of Cameroon. The study was to identify; the major causes of pre and post harvest losses, the management techniques adopted to overcome these losses, the socio economic characteristics of farmers that influence the adoption of the techniques. The multistage random sampling technique was used to get a sample of 120 rice farmers, from whom necessary information were elicited using questionnaires. Data were analyzed with descriptive statistics and binomial logit model. The results revealed that marital status, quantity of grains harvested, membership into a common initiative group and surface area cultivated were statistically significant factors influencing adoption of pre and post harvest management techniques. Also household size, farming experience and farm type were positively and statistically not significant factors while gender, age of farmer, level of education and income level affected adoption negatively and were not statistically significant Lack of financial incentives, inadequate machinery, poor soils, were major constraints faced by respondents. It was recommended that all factors that significantly affect adoption of technologies be improved.